Leksikon nelayan Karangsong sebagai identitas bahasa masyarakat pesisir Indramayu: Kajian etnolinguistik - Alfien, Moh. Fajrul; Rakhmawati, Ani (Universitas Mulawarman, 2026)
Karangsong is the largest fishing village in Indramayu. The Karangsong community, dominated by fishermen, has a distinctive linguistic identity reflected in the lexicon of maritime activities understood only by the local coastal people. Therefore, it is important to explore this lexicon as an effort to document the linguistic wealth of the Indramayu coastal community. This study aims to: (1) describe the linguistic situation of the Karangsong community; (2) identify the lexicon of fish names, fishing transportation, ship parts, fishing equipment, and fishing activities; and (3) explore the cultural portrait of the Karangsong community. This research employs a qualitative descriptive method with an ethnolinguistic approach. The data consist of the linguistic activities of the Karangsong coastal community collected through observation, in-depth interviews, and questionnaires involving captains, boat builders, fishermen, and local residents. The results show that: (1) the Karangsong community has a wide variety of marine lexicon understood only by Indramayu’s coastal people; (2) this lexicon appears in the naming of fish, boats, boat parts, fishing tools, and activities; and (3) besides distinctive linguistic characteristics, the Karangsong community also holds beliefs, traditions, and folklore that shape their cultural identity.